Textual Dissidence: The Occasions of Wilde’s ‘The Soul of Man under Socialism’ - Mackie, Gregory (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2013)
“The Soul of Man under Socialism” is unique among Oscar Wilde’s essays because it was published as a book during his lifetime. As The Soul of Man, it appeared five days after his sentencing to two years’ imprisonment. Issued by family friend Arthur Humphreys, The Soul of Man was published in a modest, privately printed edition limited to fifty copies. Wilde’s essay provided Humphreys with an opportunity to combat injustice with idealism. Humphreys’ edition went further, intensifying Wilde’s denunciation of a punitive society by emending the essay’s text, specifically by deleting the word “occasional” from Wilde’s critique of crime and punishment. Indeed, the essay’s strident indignation derives from a sense of solidarity with identities considered deviant by public opinion, which, I argue, was precisely Humphreys’ purpose when he pointedly published The Soul of Man in 1895.